2009
DOI: 10.1086/605576
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Moxifloxacin in Cerebrospinal Fluid and Plasma in Patients with Tuberculous Meningitis

Abstract: Moxifloxacin cerebrospinal fluid (CSF) penetration was evaluated by obtaining full plasma and CSF time concentration curves for 4 patients with tuberculous meningitis. The geometric mean ratio of the areas under the curve for CSF to plasma were 0.82 (range, 0.70-0.94) at 400 mg once per day and 0.71 (0.58-0.84) at 800 mg once per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 14 publications
0
70
0
Order By: Relevance
“…However, limited studies seem to suggest the safety of higher doses. A recent study by Ruslami et al (40) which evaluated daily 800-mg doses of moxifloxacin did not show increased toxicity, while a study by Alffenaar et al showed tolerability at 600 mg and 800 mg moxifloxacin (41). An ongoing clinical trial by Alffenaar et al is evaluating the safety of moxifloxacin at escalated doses of 600 and 800 mg (NCT01329250; http://clinicaltrials.gov /show/NCT01329250).…”
Section: Discussionmentioning
confidence: 99%
“…However, limited studies seem to suggest the safety of higher doses. A recent study by Ruslami et al (40) which evaluated daily 800-mg doses of moxifloxacin did not show increased toxicity, while a study by Alffenaar et al showed tolerability at 600 mg and 800 mg moxifloxacin (41). An ongoing clinical trial by Alffenaar et al is evaluating the safety of moxifloxacin at escalated doses of 600 and 800 mg (NCT01329250; http://clinicaltrials.gov /show/NCT01329250).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the AUC CSF /AUC S ratio, their penetration into the CSF in the absence of meningeal inflammation is much higher than that of ␤-lactam antibiotics (see Table S1.1 in the supplemental material). Fluoroquinolones are of great value for the treatment of CNS infections by Gram-negative aerobic bacilli (ciprofloxacin) and by Mycobacterium tuberculosis (moxifloxacin) (4,5). The activity of most fluoroquinolones is too low to treat Streptococcus pneumoniae meningitis (176).…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…The CSF penetrations of ethambutol and of the larger compounds streptomycin (hydrophilic) and rifampin (lipophilic; plasma protein binding rate of approximately 80%) are lower, and these compounds do not always reach CSF concentrations that are active against M. tuberculosis, in particular when meningeal inflammation is less pronounced or resolves during reconvalescence (106). When resistant strains of M. tuberculosis cause meningitis, moxifloxacin reaches high CSF concentrations in the presence and absence of meningeal inflammation and has been used successfully for this indication (4,5). The entry of isoniazid, pyrazinamide, rifampin, and streptomycin into CSF during tuberculous meningitis was not inhibited by concomitant corticosteroid treatment (20 mg dexamethasone/ day i.v.…”
Section: Antituberculosis Drugsmentioning
confidence: 99%
“…The optimal fluoroquinolone agent and exposure for TBM treatment have not been defined. There have been case reports or small case series describing ciprofloxacin, levofloxacin, and moxifloxacin pharmacokinetics (PKs) in TBM treatment (1,2,4,7,13,38), but there are no clinical data evaluating gatifloxacin or fluoroquinolone exposure-response relationships for this patient population.…”
mentioning
confidence: 99%